A New Python Library for the Manipulation and Annotation of Linguistic Sequences (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
The Python package linse (https://pypi.org/project/linse) offers various methods for the manipulation and annotation of sequences. In this short overview, we summarize its major functionalities and provide some information on its background and how we intend to develop it further in the future.
Keywords: sequence manipulation; sequence annotation; computational historical linguistics; historical language comparison; linguistic sequences